Older adults’ lived experiences with bamboo bed handicrafts in improving their quality of life - Sangsuk, Nisachon; Meethien, Nongyaow; Khamenkan, Kanokjun; Wongkruasorn, Watcharawan; Pongprathet, Jarurin; Shangyom, Duangtida (Jurnal Keperawatan Padjadjaran, 2024)
Background: Improving the quality of life for older adults is crucial in Northeast, Thailand, where most have low health literacy and live in substandard conditions. They are more likely to age alone or with a spouse with less support overall. Purpose: This study aimed to explore how the older adults had lived experiences using local wisdom, knowledge, and skill of bamboo bed handicrafts to improve their quality of life and strengthen the community. Method: This research study used a descriptive design based on Husserl’s qualitative phenomenological philosophy. Participants were purposively chosen. The semi-structured interview guide was created. The twelve key informants, aged 61 to 78 years, had knowledge and experience of making bamboo bed crafts and were interviewed face-to-face in their home environment by consent. Seniors with cognitive impairment met the exclusion criteria. Guba and Lincoln’s trustworthiness criteria were used. The content analysis used the Colaizzi method. Result: This study found four main themes: 1) Meaningful life 2) Happy life 3) Happy society and 4) Coping with deteriorating physical health through resilience adaptation. Conclusion: Nurses should enhance quality of life for older adults by supporting their psychological well-being through self-acceptance, coping, resilient adaptation, and continued activity.